The Impact of Digital Transformation and Digital Culture on the Perceived Sustainability of Organizational Performance through Hybrid Work Effectiveness: Evidence from a Marketing Research Company (PT XYZ) - Intan Rosefine; Dodie Tricahyono (AGUSPATI Research Institute, 2026)
Abstract This study investigates the impact of digital transformation and digital culture on perceived sustainable corporate performance, specifically examining the mediating role of hybrid work effectiveness. Facing operational challenges and declining service quality, organizations must understand how to effectively execute digital strategies. A quantitative approach utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to primary data collected from 130 purposively selected employees at PT XYZ, an Indonesian marketing research firm. The findings demonstrate that digital transformation and digital culture significantly enhance hybrid work effectiveness. Crucially, the direct effect of digital culture on sustainable performance is insignificant but is fully mediated by hybrid work effectiveness, while digital transformation exhibits partial mediation. These results highlight that advanced technological infrastructure and an innovative digital mindset require a highly coordinated hybrid work system as an execution engine to secure long-term operational stability and sustainable corporate performance.